2022
DOI: 10.1093/brain/awac198
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of spinal and bulbar muscular atrophy in South Korea: a cross-sectional study of 157 patients

Abstract: Spinal and bulbar muscular atrophy, namely Kennedy disease, is a rare progressive neurodegenerative disorder caused by the expansion of a CAG repeat in the first exon of the androgen receptor gene on the X chromosome. We assessed the clinical history, laboratory findings, functional scales, and electrophysiological data, as well as the levels of luteinizing hormone, follicle-stimulating hormone and testosterone, in 157 Korean patients with genetically confirmed spinal and bulbar muscular atrophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…27 Additionally, serum creatinine levels begin to decline in patients with SBMA >10 years before the onset of muscle weakness and continue to decline with clinical progression. 4,10,28 In this study, whole-body muscle MRI confirmed that serum creatinine levels decreased with the progression of fat infiltration, consistent with previous studies' findings. Serum creatinine appears to be a promising biomarker for assessing muscle mass in patients with SBMA.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…27 Additionally, serum creatinine levels begin to decline in patients with SBMA >10 years before the onset of muscle weakness and continue to decline with clinical progression. 4,10,28 In this study, whole-body muscle MRI confirmed that serum creatinine levels decreased with the progression of fat infiltration, consistent with previous studies' findings. Serum creatinine appears to be a promising biomarker for assessing muscle mass in patients with SBMA.…”
Section: Discussionsupporting
confidence: 92%
“…[34][35][36] FSH and LH levels tend to be elevated from their normal values. 30 Furthermore, LH levels demonstrate negative correlation with clinical scales, 4 whereas testosterone levels demonstrate positive correlation with the clinical scales. 4,11 In this study, the FSH levels increased as the fat infiltration progressed (see Fig 3); however, the levels of LH and testosterone remained relatively constant (Fig S2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations